Influence of Diabetes on Physical Function among the Elderly Persons - Tabassum, Farzana; Flora, Meerjady Sabrina (Ibrahim Medical College Journal, 2010)
There is growing recognition that the complications associated with type-2 diabetes may translate into functional impairments in older people. This cross sectional study was conducted between January and June 2008 to determine the influence of diabetes on physical functions in an elderly (≥55 years) population. Fifty-five elderly diabetics attending the out-patient department of a diabetic centre were selected by convenient sampling and compared with fifty-five non-diabetic elderly persons of the near-by community. Their physical functions were assessed by Barthel Index, SF-36 Health Survey and Modified Physical Performance test. Diabetic elderly persons, on average, obtained lower scores in all these three tests. After removing the effect of socio-demographic variables, influence of diabetes on level of independence measured by Barthel Index did not persist. However, the difference in SF-36 health survey and Modified Physical Performance test scores between diabetics and non-diabetics remained significant after controlling for socio-demographic variables. The current study showed influence of diabetes on physical functions in the elderly. People should be motivated and guided properly to practice a healthy lifestyle in order to prevent and control diabetes and thus avoid complications of diabetes mellitus and disabilities in later life. Ibrahim Med. Coll. J. 2009; 3(2): 45-49 Keywords: Diabetes mellitus, Physical function, Barthel Index, Short Form-36 Health Survey, Modified Physical Performance Test. DOI: 10.3329/imcj.v3i2.4162